On the Origins of the Word "Substance" - Maryniarczyk, Andrzej (Peitho. Examina Antiqua, 2017)
The present article discusses the emergence of the term “substance” (ousia). It is shown that while the word obviously has its roots in Greek language and tradition, it presupposes a much broader context. Thus, to comprehend the full meaning of the term one must take into account the whole philosophical tradition in which it occurs and the whole of reality to which it refers. Furthermore, it is demonstrated that from the very beginning ousia (substantia) was linked to that which exists actually and constitutes the internal principle (essence) of being. This causal nature of the substance is frequently overlooked and the sense of the word is very often reduced to an eternal and immutable substrate (i.e., something static and unchanging).